Analisis Yuridis Temuan Insidental dalam Praktik Penyadapan Komisi Pemberantasan Korupsi - Ade Rachmad Hidayat; Arne Huzaimah; K.A. Bukhori (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines the normative construction of the Indonesian Corruption Eradication Commission's (KPK) wiretapping authority, specifically concerning "wiretapping beyond the main case" or incidental findings. The analysis focuses on the tension between KPK's extraordinary powers in combating corruption and the constitutionally guaranteed right to privacy. Using a normative legal research approach, this study evaluates the conformity of extended wiretapping practices with human rights limitation principles, including legality, necessity, proportionality, and due process of law. Findings reveal normative ambiguity in existing regulations, which could lead to broad discretion and potential violations of constitutional rights. The research proposes an ideal formulation for wiretapping authority limits, emphasizing strict subject and object restrictions, judicial authorization, time limitations, and independent oversight. This framework aims to achieve a balance between effective corruption eradication and the protection of human rights within a democratic rule of law.